The epidemiology of hand eczema in the general population - prevalence and main findings - Thyssen, Jacob P.; Johansen, Jeanne D.; Linneberg, Allan; Menné, Torkil (Contact dermatitis, 2010)
Numerous studies have investigated the prevalence and risk factors of hand eczema in the general population. These studies are of high value as they tend to be less biased than studies using clinical populations and as they are important for healthcare decision makers when they allocate resources. This study aimed to review the epidemiology of hand eczema in the general population. Literature was examined using Pubmed‐Medline, Biosis, Science Citation Index, and dermatology text books. On the basis of studies performed between 1964 and 2007, the point prevalence of hand eczema was around 4%, the 1‐year prevalence nearly 10%, whereas the lifetime prevalence reached 15%. Based on seven studies, the median incidence rate of hand eczema was 5.5 cases/1000 person‐years (women = 9.6 and men = 4.0). A high incidence rate was associated with female sex, contact allergy, atopic dermatitis, and wet work. Atopic dermatitis was the single most important risk factor for hand eczema. Hand eczema resulted in medical consultations in 70%, sick leave (> 7 days) in about 20%, and job change in about 10%. Mean sick time was longer among those with allergic hand eczema than those with atopic and irritant hand eczema. Moderate to severe extension of hand eczema was the strongest risk factor for persistence of hand eczema. Other risk factors included early onset of hand eczema and childhood eczema. The aetiology of hand eczema is multifactorial and includes environmental as well as genetic factors. Future studies should focus on unresolved areas of hand eczema, for example, genetic predisposition.